2021
DOI: 10.1186/s12903-021-01687-w
|View full text |Cite
|
Sign up to set email alerts
|

A logistic analysis prediction model of TMJ condylar erosion in patients with TMJ arthralgia

Abstract: Background In terms of diagnostic and therapeutic management, clinicians should adequately address the frequent aspects of temporomandibular joint (TMJ) osteoarthritis (OA) associated with disk displacement. Condylar erosion (CE) is considered an inflammatory subset of OA and is regarded as a sign of progressive OA changes potentially contributing to changes in dentofacial morphology or limited mandibular growth. The purpose of this study was to establish a risk prediction model of CE by a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…Remarkably, joints with ADDNR were more likely to develop erosion, osteophytes and cysts than those with ADDR. Only subcortical sclerosis was associated with increasing age, as reported by Gynther et al 50 Several factors have been reported as risk items for the development of erosion, including gender, age, systemic, hormonal and mechanical factors, such as disc displacement, occlusion, trauma and increased joint friction 51 . Therefore, DDs may not be the only contributor to erosion.…”
Section: Discussionmentioning
confidence: 63%
“…Remarkably, joints with ADDNR were more likely to develop erosion, osteophytes and cysts than those with ADDR. Only subcortical sclerosis was associated with increasing age, as reported by Gynther et al 50 Several factors have been reported as risk items for the development of erosion, including gender, age, systemic, hormonal and mechanical factors, such as disc displacement, occlusion, trauma and increased joint friction 51 . Therefore, DDs may not be the only contributor to erosion.…”
Section: Discussionmentioning
confidence: 63%
“…Only in patients with TMD and condylar erosive changes, as well as those with condylar osteophytosis a closer position of the malleus to PTF was noted. Condylar erosion is a symptom of ongoing osteoarthritic alterations that may be linked to altered dentofacial morphology [ 21 ]; thus, bone erosions may be associated with disc displacement. Moreover, condylar erosion was found to be a major contributor to a painful disc displacement without reduction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Emshoff et al, 33 in patients with TMJ arthralgia, missing posterior teeth effectively predict condyle erosion.…”
Section: Discussionmentioning
confidence: 99%